Scenarios for the future of the German confectionary market by 2030 - strategic implications for Ferrero Germany: explore - megatrend 1 and megatrend 2 - Nicolai, Francesco (2023)
The Work Project explores the future of the German confectionery market, employing the intuitive logical school in scenario planning. The study focuses on extensive expert and client involvement, particularly collaborating with Ferrero Deutschland GmbH. The primary objective is to navigate high uncertainty, understand plausible events' impacts on industry, retail, and consumers, and dynamically respond to an unknown future. The development of four plausible scenarios, centered on the key uncertainties “Stability of Supply Chain” and “Health Regulations”, contributes to fostering a heightened awareness. General and scenario-specific strategic implications, offering action plans for the four distinctive futures for Ferrero Deutschland GmbH are provided.